Spatial heterogeneity study of early child marriages before and after implementation of prohibition of Child Marriage Act (2006) in India: Evidence from NFHS - Singh, Anuj; Bahadur, Bajarang; Gupta, Jagriti (Brazilian Journal of Biometrics, 2025)
Despite numerous laws, rights, and well-known health concerns, child marriage remains to be prevalent in developing countries such as India. This practice is fueled by a complex interaction of social and normative attitudes and values that are understated in national and even state-level assessments of child marriage drivers. This study aims to assess the spatial pattern and associated factors of early-marriage before and after Prohibition of Child Marriage Act in Indian districts among reproductive aged women. Univariate and Bivariate analysis, Multiple logistic regression, Moran’s I Statistics and Regression analysis (OLS and Spatial Error/Lag Model) were carried out for the analysis of data in our study. The data came from the fourth round of the National Family Health Survey (2015-16).This study finds wide inter districts heterogeneity in levels of child marriage, one decade before and after prohibition of child marriage across India. The prevalence of child marriage has substantially declined (nearly 21%) after implementation of prohibition of child marriage act. Bivariate Moran’s I value for rural was found to be highest 0.76 and 0.72 before and after implemented act respectively suggesting high spatial auto-correlation of early-marriages in the rural-districts of India. The findings of this study show that the prevalence of child marriage has substantially declined after implementation of child marriage act but this declining trend of child marriage has been accompanied by many factors apart from enforcement of laws against child marriage practice. Furthermore, future child marriage programs and policies should take into account improving economic status, enhancing female sovereignty and marital decision-making in the home, as well as the geographic, social, and normative aspects of the local community.